The correctional orientation of community corrections: Legislative changes in the legally prescribed functions of community corrections 1992–2002 - Steiner, Benjamin (American journal of criminal justice, 2005)
Over the years, the prevailing correctional orientation in the United States has shifted back and forth between punishment and rehabilitation. These changes in correctional ideology are typically marked by differing sentencing practices and changing criminal justice research agendas. On the other hand, how corrections is legally mandated to operate is less understood. In 1993, Johnson, Dunaway, Burton, Marquait, and Cuvelier assessed the legally prescribed functions of community corrections for all 50 states and classified them as either reform or control oriented functions. They concluded the majority of states were primarily reform oriented. In this study, we replicate Johnson et al.’s (1993) methods using the statutes from all 50 states in 2002. However, we classified our findings, as well as recoded Johnson et al.’s (1993) findings, into punishment or rehabilitation functions. We make comparisons between 1992 and 2002 for the purpose of assessing where legally mandated orientation of community corrections stands today on the punishment/rehabilitation debate.